ENVIRONMENTAL AND HEALTH EFFECTS OF AIR POLLUTION AND THE SOLUTIONS (A CASE STUDY OF AWKA NORTH LOCAL GOVERNMENT AREA OF ANAMBRA STATE, NIGERIA). - Eguvbe , Peter M.; Avbunudiogba, Rosemary E.; Ogonegbu, Augustine C.; Anyanwu, Jacinta A. (Science Journal of University of Zakho, 2024)
Air pollution has long been a major global concern in developing countries, posing serious health and environmental challenges. The awareness of the effects of air pollution on human health and the environment and various ways to mitigate the impact of air pollution was investigated in Awka, Anambra State. The population size was 1000. In carrying out this research, three hypotheses were postulated and tested at a 5% level of agreement. A well-structured questionnaire was used to collect data from the subjects, and simple percentages, and weighted mean statistics were used to analyze the data. In contrast, the Chi-square was used in testing the hypotheses. Results reveal that over 50 % of the residents of Awka are fully aware of the air pollution problem in the town and are knowledgeable about the dangers of air pollution. Air pollution is prevalent in Awka town, which is largely caused by heavy traffic resulting in increased vehicular emissions of poisonous gases. The findings show that air pollution significantly negatively impacts human health and the environment. The study recommends awareness creation, enactment of suitable legislation, and activities that promote air pollution, such as open incineration of wastes and bush burning, especially for agricultural purposes, should be discouraged. We underscore the necessity of facilitating more research on the associations between exposure and health in marginalized communities that are disproportionately affected by air pollution yet inadequately represented in existing investigations.